2021
DOI: 10.3389/fpsyg.2021.657952
|View full text |Cite
|
Sign up to set email alerts
|

Autism Case Report: Cause and Treatment of “High Opioid Tone” Autism

Abstract: Introduction: Neurobiological systems engineering models are useful for treating patients. We show a model of “high opioid tone” autism and present a hypothesis about how autism is caused by administration of opioids during childbirth.Main Symptoms: Clinical diagnosis of autism in a 25 year old man was confirmed by a Social Responsiveness Scale (SRS) self-rating of 79, severe, and a Social Communications Questionnaire (SCQ-2) by the patient's father scoring 27. Cold pressor time (CPT) was 190 seconds—unusually… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 10 publications
(14 citation statements)
references
References 17 publications
0
14
0
Order By: Relevance
“…Although allied research in humans has suggested that opioids like buprenorphine might reduce separation distress and offer treatment for some forms of depression (Panksepp and Yovell, 2014;Yovell et al, 2016), there have also been concerns that opioids may usurp healthy parent-infant separation distress and reward circuits that may be critical to mother-infant bonding (Swain et al, 2005). Indeed, "high opioid tone" has been recently discussed as a concern in the development of autism spectrum disorder (Anugu et al, 2021), which is arguably one of several developmental disorders showing impaired intersubjective function (Trevarthen and Aitken, 2001). Thus, although BT is highly effective for reducing withdrawal, intersubjectivity-dependent face mirroring may be adversely influenced.…”
Section: Discussionmentioning
confidence: 99%
“…Although allied research in humans has suggested that opioids like buprenorphine might reduce separation distress and offer treatment for some forms of depression (Panksepp and Yovell, 2014;Yovell et al, 2016), there have also been concerns that opioids may usurp healthy parent-infant separation distress and reward circuits that may be critical to mother-infant bonding (Swain et al, 2005). Indeed, "high opioid tone" has been recently discussed as a concern in the development of autism spectrum disorder (Anugu et al, 2021), which is arguably one of several developmental disorders showing impaired intersubjective function (Trevarthen and Aitken, 2001). Thus, although BT is highly effective for reducing withdrawal, intersubjectivity-dependent face mirroring may be adversely influenced.…”
Section: Discussionmentioning
confidence: 99%
“…There is an interesting hypothesis reported early in the literature that assumed opioid excess in the brain is a cause or a factor of autistic features. A recent case report hypothesized a “high opioid tone” group of autistic patients [ 170 , 171 , 172 ]. However, the use of opioid receptor antagonist naltrexone to overcome such excess resulted in a significant reduction in hyperactivity without any improvement in the core symptoms of ASD [ 173 ].…”
Section: Endogenous Neuromodulators and Pharmacological Agents In Bra...mentioning
confidence: 99%
“…In terms of the social instincts, the person exposed to the extreme or ambivalent separation-distress trauma will experience difficulties in their relationships with others. Johnson (65)(66)(67)(68) has extensively worked on an opioid-tone model that hypothesizes a correlation between opioid tone and proximity to others. If a person feels lonely, their opioid tone is low and can be modulated by the company of others.…”
Section: Seeking Pleasure and Rewards: The Frequent Misunderstandings About Addictionmentioning
confidence: 99%
“…The second category entails the modulation of the need for proximity to others ( 66 ). High opioid tone contributes to the subjective feeling that the person does not need to relate to others as can be seen in Autism Spectrum Disorder (ASD) ( 65 ). This feeling may cause the pleasurable idea of self-sufficiency, which would apparently solve the problem of failed trust derived from early childhood separation-distress trauma.…”
Section: Introductionmentioning
confidence: 99%